Rule Prioritisation Heuristic in Shift Design of Airline Ground Crew - Kong Weng, Lee (Lee Kong Weng, 2024)
In various industries, the exigency of workforce shift scheduling and rostering demands immediate, innovative solutions. Many off-the-shelf scheduling products lack the flexibility to adapt to varied organizational requirements, resulting in widespread reliance on manual interventions. This research, rooted in a case study of a local airline at Kuala Lumpur International Airport (KLIA), a major regional hub, endeavours to formulate an algorithm addressing workforce shift scheduling and rostering complexities. The proposed algorithm aims to ensure judicious allocation of operational tasks, emphasizing minimal workforce utilization, reduced idleness, and heightened adaptability in employee schedules. Utilizing an existing workforce prediction method and shift design criteria, the study determines the minimum workforce required for task completion. Shifts are assigned based on this minimum, employing heuristic and genetic algorithms. Subsequent optimization of potential schedules culminates in the identification of the most efficacious ones. Empirical tests reveal the proposed heuristic method's superiority over manual practices and genetic algorithms. It not only minimizes shift idle time and aligns with optimal shift starting times but also significantly reduces workforce requirements, streamlining the shift scheduling process, irrespective of data size. This research contributes valuable insights to the advancement of workforce management strategies, offering practical and innovative solutions within the specified context.